Effects of annealing on electrical and optical properties of a multilayer InAs/GaAs quantum dots system - Chiquito,Adenilson José (2004)
A systematic investigation of the properties of the InAs/GaAs self-assembled quantum dots (SAQDs) system subjected to a post-growth annealing using capacitance-voltage, Raman scattering and photoluminescence measurements is presented. The application of both electrical and optical methods allowed us to obtain reliable information on the microscopic structural evolution of this system. The single layer and the multilayer quantum dots were found to respond differently to the annealing process, due to the differences in strain that occur in both systems. The diffusion activated by strain provoked the appearance of an InGaAs alloy layer in substitution to the quantum dots layers; this change occurred at the annealing temperature T = 600 ºC in the multilayer system. A single dot layer, however, was observed even after the annealing at T = 700 ºC. Moreover, the low temperature annealing was found to improve the homogeneity of the multilayer system and to decrease the electrical interlayer coupling.